HUBUNGAN DUKUNGAN ORANG TUA DAN FAKTOR YANG MEMPENGARUHI PERILAKU MAKAN JAJAN DI SEKOLAH DASAR DI SD MUHAMMADIYAH 1 KOTA PEKANBARU - Nurpelita Sembiring (Universitas Negeri Medan, 2018)
ABSTRACTThe purpose of this research is to analyze the support of parents in the snack feeding of elementary students of Muhammadiyah 1 Pekanbaru, to analyze the factors that influence the snack food behavior of the students of SD Muhammadiyah 1 Pekanbaru and to analyze the relationship of parent support to the dominant factor of the students' snack food. The study was conducted in November 2016. Based on the calculation of data analysis of parent and fakktor support that influence student's snack behavior, it is known that the result of parent support parent calculation shows reassurance of worth 15 students (45,5%), social integration (social integration) 14 students (43, 4%), opportunity to nurturance (opportunity to help) 14 students (43.2%), emotional attachment of 13 students (38.2%), reliable alliance (12 reliable students) 34.8%) and guidance of 11 students (34.1%). Also known as the result of the calculation, the percentage of snack behavior showed 19 students (57.6%), felt fit with school snack, 18 students (55.9%), desire to get a higher job 17 students (52.5%), and motivation 14 students (43,7%). The dominant factor of both variables is the interest variable on the indicator of ideals with a percentage of 57.6%. Keywords: Parent Support, Factors that influence snack behavior